2021
DOI: 10.1038/s42003-021-01886-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of LIM domain-dependent recruitment of paxillin to αvβ3 integrin-positive focal adhesions

Abstract: The LIM domain-dependent localization of the adapter protein paxillin to β3 integrin-positive focal adhesions (FAs) is not mechanistically understood. Here, by combining molecular biology, photoactivation and FA-isolation experiments, we demonstrate specific contributions of each LIM domain of paxillin and reveal multiple paxillin interactions in adhesion-complexes. Mutation of β3 integrin at a putative paxillin binding site (β3VE/YA) leads to rapidly inward-sliding FAs, correlating with actin retrograde flow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 91 publications
1
28
0
Order By: Relevance
“…It is also possible that the exceptional abundance of lysine residues within the paxillin LD motifs and the LIM4 domain revealed interactions that are only short lived or not occurring in a physiological context. The NMR structure of the kindlin F0 domain complexed with paxillin LIM4 domain ( Zhu L. et al, 2019 ) is consistent with the recently proposed orientation of paxillin within the FA complex, and with the interaction of its positively charged LIM4 domain with the plasma membrane ( Kanchanawong et al, 2010 ; Ripamonti et al, 2021 ) ( Figure 1 ). Interestingly, the disposition of proteins within adhesions has been also addressed by means of a proximity biotinylation assay (BioID), which revealed that the paxillin N-terminus could extend for ∼25 nm into the cytoplasm, and accommodate interactions within the intermediate zone of FAs, where are situated proteins that cannot be detected by using kindlin2 as BioID probe ( Dong et al, 2016 ).…”
Section: The β 3 Integrin-talin1-kindlin-paxillin ...supporting
confidence: 86%
See 2 more Smart Citations
“…It is also possible that the exceptional abundance of lysine residues within the paxillin LD motifs and the LIM4 domain revealed interactions that are only short lived or not occurring in a physiological context. The NMR structure of the kindlin F0 domain complexed with paxillin LIM4 domain ( Zhu L. et al, 2019 ) is consistent with the recently proposed orientation of paxillin within the FA complex, and with the interaction of its positively charged LIM4 domain with the plasma membrane ( Kanchanawong et al, 2010 ; Ripamonti et al, 2021 ) ( Figure 1 ). Interestingly, the disposition of proteins within adhesions has been also addressed by means of a proximity biotinylation assay (BioID), which revealed that the paxillin N-terminus could extend for ∼25 nm into the cytoplasm, and accommodate interactions within the intermediate zone of FAs, where are situated proteins that cannot be detected by using kindlin2 as BioID probe ( Dong et al, 2016 ).…”
Section: The β 3 Integrin-talin1-kindlin-paxillin ...supporting
confidence: 86%
“…Paxillin is composed of two modules ( Figure 1 ): an unstructured amino-terminal half, comprising five leucine- and aspartic acid-rich motifs (with the consensus LDXLLXXL and thus named LD) forming short amphipathic α -helices ( Bertolucci et al, 2005 ); and a carboxyl-terminal half composed of four LIM domains, each folded in two consecutive zinc fingers ( Freyd et al, 1990 ; Velyvis et al, 2001 ). Recruitment of paxillin to FAs is mediated by the array of LIM domains, while its signaling capacity mostly relies on the N-terminal LD motif containing sequences ( Brown et al, 1996 ; Ripamonti et al, 2021 ) ( Figure 2B ).…”
Section: The β 3 Integrin-talin1-kindlin-paxillin ...mentioning
confidence: 99%
See 1 more Smart Citation
“…10,41 Meanwhile, kindlin-3 may recruit paxillin via its F0 subdomain binding to the LIM4 domain of paxillin, which may further facilitate talin binding to the integrin β3 CT by forming a multiprotein complex. 28,45 Upon ligand occupation, integrin αIIbβ3 outside-in signaling is initiated and additional cytoplasmic/cytoskeletal signaling adaptors are recruited to the integrin β3 CT, during which paxillin binding to the PH domain of kindlin-3 via its LIM3 domain may occur and play a key role in supporting integrin αIIbβ3 outside-in signaling in platelets (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the vastly high number of molecules that function in cell adhesion under physiological and pathological processes, the agglomeration of proteins within focal adhesion has been termed cancer cellular adhesome to discriminate them from randomly distributed surrounding proteins (Maziveyi and Alahari, 2017 ). The contributing proteins of the adhesome can be divided into four different branches of the basic adhesion system which includes the Talin-Vinculin (Mierke et al, 2008a , 2010 ; Golji et al, 2011 ; Wang et al, 2019 ; Boujemaa-Paterski et al, 2020 ), FAK-Paxillin (Hu et al, 2015 ; Mierke et al, 2017 ; Ripamonti et al, 2021 ), α-Actinin-Zyxin-VASP (Oldenburg et al, 2015 ), and ILK-PINCH-Kindlin biochemical signal transduction pathways (Honda et al, 2013 ; Horton et al, 2015 ; Kunschmann et al, 2017 ). All of them represent critical pathways or mechanosensory systems to respond to changes in the mechanical homoestatic stage of cells.…”
Section: Introductionmentioning
confidence: 99%